A STANDALONE SAMBA-NIS/NFS SERVER MODEL FOR WINDOWS AND LINUX DUAL BOOT CLIENTS WITH INDIVIDUAL USER AUTHENTICATION - Adikaram, K.K.L.B.; Andrahannadi, D.T.; Piyaratne, M.K.D.K.; Wijewardana, D.S.R.; Navaratne, C.M. (European Scientific Journal, ESJ, 2014)
Maintaining several file servers is a management as well as financial overhead to an origination. We introduce a standalone SAMBA-NIS/NFS server model for Windows and Linux dual boot clients with individual user authentication and common home folder is proposed for schools or universities. We used NIS (Network Information Service), NFS (Network File System), SAMBA, Fedora and Windows for configuration. This model serves requests from both Windows and Linux clients with generic user name and password. Individual user authentication (IUA) is guaranteed: a separate profile is accommodated for each individual user with common home folders for both Windows and Linux platforms. Four year observation results show that the developed model is consistent and the overall system performance is significantly higher than that of the system with two servers. Further the system is efficient and error free in terms of maintenance and concurrent access to large numbers of users. This model can be implemented in schools or university computer laboratories, and, is economically more suitable for small scale network systems.